2011
DOI: 10.1007/s10035-010-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of undrained adiabatic shearing of a rock layer with Cosserat microstructure

Abstract: International audienceStability of undrained shearing in a classical Cauchy continuum has been first analyzed by Rice [1] who showed that instability occurs when the underlying drained deformation becomes unstable (i.e. in the softening regime of the corresponding drained stress-strain curve). However Vardoulakis [2, 3] has shown that Rice's linear stability analysis, if performed at the state of maximum deviator, leads to a sharp transition from infinitely stable to infinitely unstable behaviour, which indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 17 publications
3
58
0
Order By: Relevance
“…The values of the different parameters are chosen to represent a fault gouge at a seismogenic 165 depth of 7km, which is a typical centroidal depth for crustal faults. Furthermore, as this set of parameters was used in previous studies, we can compare our results to foregoing works on the subject and complement them (Rice, 2006, Sulem et al, 2011. The rotations are imposed at the upper and lower boundaries (ω The Drucker-Prager yield criterion is generalized for Cosserat continua, as in Rattez et al (2017a) with a friction coefficient which evolves with plastic shear deformation:…”
Section: Problem Statement and Mesh Convergencementioning
confidence: 87%
“…The values of the different parameters are chosen to represent a fault gouge at a seismogenic 165 depth of 7km, which is a typical centroidal depth for crustal faults. Furthermore, as this set of parameters was used in previous studies, we can compare our results to foregoing works on the subject and complement them (Rice, 2006, Sulem et al, 2011. The rotations are imposed at the upper and lower boundaries (ω The Drucker-Prager yield criterion is generalized for Cosserat continua, as in Rattez et al (2017a) with a friction coefficient which evolves with plastic shear deformation:…”
Section: Problem Statement and Mesh Convergencementioning
confidence: 87%
“…Following Sulem et al (2011), we assume a Terzaghi decomposition of the stress tensor in effective stress s' ij and pore pressure p (s ij~s ' ij {pd ij ) and assume a Coulomb yield stress and plastic potential for the effective stresses…”
Section: Constitutive Equations Of Elasto-plasticitymentioning
confidence: 99%
“…If the temperature is increased in undrained conditions, so that thermal pressurisation is active, Sulem et al (2011) showed that, even in the absence of dilatancy, the shear band will be formed in the hardening regime H . 0.…”
Section: Bifurcation Pointmentioning
confidence: 99%
See 2 more Smart Citations